The Development and Validation of Quality of Life Scale for Iraqi Patients with Type 2 Diabetes Mellitus - Mikhael, Ehab M (J Pharm Bioallied Sci, 2020)
BACKGROUND AND AIM: The current trend for determining the effectiveness of new treatment or services provided for diabetes mellitus (DM) patients is based on assessing the improvement in both glycemic control and the patient quality of life. Many scales have been developed to assess quality of life among DM patients, but unfortunately, no one can be considered as gold standard. Therefore, this study aimed to develop and validate a brief and specific scale to assess quality of life among Iraqi type 2 DM patients. METHODS: An extensive literature review was done using Google-Scholar and PubMed to find out scales that utilized to assess quality of life among DM patients. Four relevant scales, three diabetes specific and one general, were selected. The selected scales were carefully evaluated to find out domains that are commonly used to assess quality of life and then the items within the selected domains were reviewed to choose relevant and comprehensive items for Iraqi type 2 DM patients. Ten items were selected to formulate the quality of life scale for Iraqi DM patients (QOLSID). The content validity of QOLSID was established via an expert panel. For concurrent validity QOLSID was compared to glycosylated hemoglobin (HbA1C). For psychometric evaluation, a cross sectional study for 103 type 2 DM patients was conducted at the National Diabetes Center, Iraq. Test-retest reliability was measured by re-administering QOLSID to 20 patients 2-4 weeks later. RESULTS: The internal consistency of the QOLSID was 0.727. All items had a corrected total-item correlation above 0.2. There was a negative significant correlation between QOLSID score and the HbA1C level (-0.518, P = 0.000). A significant positive correlation was obtained after re-testing (0.967, P = 0.000). CONCLUSION: The QOLSID is a reliable and valid instrument that can be used for assessing quality of life among Iraqi type 2 DM patients.